IbM Pelatihan Pembuatan â€œKerja Masâ€ (Keripik Jagung Manis) Berbasis Agropreneur - Rizka, Muhammad Arief; Primawati, Sri Nopita; Mursali, Saidil (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2016)
Technology and science for community (IbM) program aimed to create opportunities became agropreneur (entrepreneurship based on processing agricultural products) for unemployment female through implementing training in making â€œKerja Masâ€ (Keripik Jagung Manis) whose product had economic value and could be marketed to general public. In implementing IbM program had been effort to improve knowledge and skills for female in Sesela Village in order to be able to develop business center of processing sweet corn which was affordable and could be received by public. This IbM program has implemented well through socialization activities, preparation activities, counseling material, training making Kerja Mas (keripik jagung mas), and mentoring. The result of implementing IbM program such as;(1) overall participants could make â€œkerja masâ€ product which already tested through organoleptic test, (2) â€œkerja masâ€ product had obtained license of Dinkes P-IRT to guarantee decent healthy food consumption for public; (3) the product packing of â€œkerja masâ€ was fascinating and could be marketed in public; (4) establishing Joint Business Group (KUBE) â€œkerja masâ€ wa legal as center of processing sweet corn and as effort consummate agropreneur at Sesela village, and (5) the result of IbM program could be published in Jurnal Ilmiah ISSN.